Influence of the deformed state of a road bridge on operational safety - Bondar, Ivan; Kvashnin, Mikhail; Aldekeyeva, Dinara; Bekzhanova, Saule; Izbairova, Aliya; Akbayeva, Assem (Eastern-European Journal of Enterprise Technologies, 2022)
The article deals with the issues of vehicle traffic safety on artificial constructions. Ensuring safety in the field of rail transport is an essential element in the activities of all subjects of the market of railway services, including passenger carriers. To fully study the issues of the deformed state of beam superstructures, it is necessary to conduct static and dynamic tests. Before the start of the tests, it is mandatory to check the technical condition of the artificial structure: 1) visual inspection, special checks with verification of necessary parameters; 2) carrying out control linear measurements; 3) selective determination of concrete strength by non-destructive methods. First, the static tests is conducted to determine the total deformations of each beam of the superstructure at the control point with maximum deformations of ½ L. Then dynamic tests with determination of periods of natural oscillations and deformations (stresses). Processing of the results of surveys and tests of the overpass with an assessment of the possibility of passing design loads on the road bridge, after which a dynamic passport of the transport structure is compiled. The study of the stressed state of vehicles gives a clear idea of the causes of deformations in the structural elements when analyzing the work of the span of the automobile bridge in conditions of increasing axial loads and traffic flow speeds. Deformation processes lead to defects, structural failures and accidents on the vehicle, which leads to premature wear, material damage and environmental damage. Periodic measurements of deformations (stresses) of the superstructure structure over several years will make it possible to predict changes in its condition over time and determine the remaining resource in terms of load-bearing capacity and load capacity. As a result of experimental studies, it was proved that the presented technique, developed in the classical version for detecting structural defects between a single-layer coating and a base of various types, can also work effectively in the case of non-destructive testing of multilayer structures